2009
DOI: 10.2478/v10053-008-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Specifying attentional top-down influences on subsequent unconscious semantic processing

Abstract: Classical theories assume that unconscious automatic processes are autonomous and independent of higher-level cognitive influences. In contrast, we propose that automatic processing depends on a specific configuration of the cognitive system by top-down control. In 2 experiments, we tested the influence of available attentional resources and previously activated task sets on masked semantic priming in a lexical decision task. In Experiment 1, before masked prime presentation, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 46 publications
11
42
0
Order By: Relevance
“…This assumption is also in line with many studies on masked priming effects indicating that subliminally presented stimuli generally impacted on behavior only if the prime fits the current top-down setting/current intentions (e.g., Ansorge, 2006; Kiefer, 2007; Kiefer & Brendel, 2006; Kiesel, 2009; Kiesel, Kunde, & Hoffmann, 2007; Kiesel, Kunde, Pohl, & Hoffmann, 2006; Kunde, Kiesel, & Hoffmann, 2003, 2005; Martens & Kiefer, 2009; Pohl, Kiesel, Kunde, & Hoffmann, 2010). Taken together, these results show that the effects of masked stimuli both on behavior and on attention are based on strikingly similar preconditions.…”
Section: Discussionsupporting
confidence: 85%
“…This assumption is also in line with many studies on masked priming effects indicating that subliminally presented stimuli generally impacted on behavior only if the prime fits the current top-down setting/current intentions (e.g., Ansorge, 2006; Kiefer, 2007; Kiefer & Brendel, 2006; Kiesel, 2009; Kiesel, Kunde, & Hoffmann, 2007; Kiesel, Kunde, Pohl, & Hoffmann, 2006; Kunde, Kiesel, & Hoffmann, 2003, 2005; Martens & Kiefer, 2009; Pohl, Kiesel, Kunde, & Hoffmann, 2010). Taken together, these results show that the effects of masked stimuli both on behavior and on attention are based on strikingly similar preconditions.…”
Section: Discussionsupporting
confidence: 85%
“…In these studies, directing attention to the time window, location, and/or feature of a subliminal stimulus occasioned or improved processing of that stimulus, but not up to a point that the stimulus became conscious. Other findings show the modulating influence of the amount of available attention on unconscious processing (Martens & Kiefer 2009). For instance, Pessoa et al (2002) reported that the manipulation of attention load led to more or less activity in subcortical structures, such as the amygdala, and this activity was taken as evidence of unconscious processing.…”
Section: Necessity Of Attention For Consciousnessmentioning
confidence: 97%
“…Furthermore, Ng, Chan, and Schlaghecken (2012) showed that unconscious visuo-motor processes are differentially influenced by cognitive control settings induced by specific emotional states (subclinical depression vs. anxiety). Using a novel procedure for masked priming of words and of geometrical shapes, attentional task sets were shown to influence unconscious semantic and visuo-motor processes selectively (Kiefer & Martens, 2010; Martens & Kiefer, 2009). These results demonstrate that preemptive top-down control of unconscious processes coordinates the perceptual and semantic processing streams: An attentional sensitization mechanism enhances or attenuates the responsiveness of semantic and visuo-motor processing pathways to incoming subliminal stimuli depending on the currently activated task set (Kiefer, 2007; Kiefer & Martens, 2010), thereby differentially influencing subsequent subliminal semantic and visuo-motor priming.…”
Section: Identifying General Principles Underlying Conscious and Uncomentioning
confidence: 99%